Hepatoprotective activity of ethanol extract of Pavetta Indica Linn leaves - Valte, Varkung; Singh, M. Premchand; Raleng, Indira; R. K., Losica (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Traditionally, the bark of Pavetta Indica Linn., in decoction or pulverized, is administered, especially to children, to correct visceral obstructions. The decocted leaves are used externally to alleviate the pains caused by hemorrhoids. The root, pulverized and mixed with the ginger and rice-water, is given in dropsy. A local fomentation with the leaves is useful in relieving the pain of piles. Paracetamol (PCM) toxicity generates free radicals and raised serum enzyme levels-SGPT, SGOT, Alkaline Phosphatase and S. Albumin. It causes necrosis, congested vessels, multifocal area of fatty changes nuclear disintegration, sinusoidal dilation, kuffer cell hyperplasia. The reverse is considered as the index of hepatoprotective activity. The present study is being taken up to screen hepatoprotective action of P. Indica Linn. Methods: The acute liver damage in albino rats was induced by per oral administration of a single dose of 2000mg/kg b.w. PCM suspension in 0.5% Carboxy methyl cellulose (CMC) and chronic liver damage by giving the same dose of PCM on the 7th day. The hepatoprotective activity was monitored biochemically by estimating S. transaminase, S. bilirubin and S. Protein on the 8th day of experiment. Results: Ethanol extract of P. Indica inhibited PCM induced liver toxicity in albino rats at 100mg/kg and 200mg/kg b.w as assessed by the biochemical values. Conclusions: Ethanol extract of “P. Indica” exhibited significant hepatoprotective activity.